FEATURES OF THE ORGANIZATION OF ACCOUNTING OF OWN AND RENTED FIXED ASSETS AT THE COMMERCIAL ENTERPRISE - YELISEYEVA, OKSANA; DOROHOVA, V. (Herald of Khmelnytskyi National University. Economic sciences, 2022)
In the context of the coronavirus pandemic and the crisis in Ukraine's economy, the affected industries were retail. Retailers were forced to reduce their activities, which led to significant sales of their own fixed assets, to the transition to the use of leased fixed assets, as increased the need for more efficient use and organization of accounting of own and leased fixed assets in retail. The purpose of the study is to consider the features of the organization of accounting of own and leased fixed assets on the example of a small retail business.The article analyzes the composition of fixed assets, their dynamics and structure in a commercial enterprise. Features of the organization of accounting of fixed assets are considered. Considerable attention is paid to the peculiarities of accounting for fixed assets taken into both operating and financial leases. Features of financial and operating lease of fixed assets are described. Features of depreciation and inventory of own and leased fixed assets at small retail enterprises are revealed. We compared the basic norms of own and leased fixed assets according to the Regulations (standards) of accounting and International Accounting Standards.
Keywords: fixed assets; operating lease; financial lease; leasing; trading company